A conceptual model of operational risk events in the banking sector - Suné Ferreira; Zandri Dickason Koekemoer (Cogent Economics & Finance, 2019)
Operational risk constitutes a large portion of a bank's risk exposure. Unlike other financial risks, operational risk is classified as a pure risk (only an opportunity of a loss), as it always leads to a financial loss for a bank. The failure to mitigate and manage operational risk effectively during past operational risk events has led to the demise of several banks and other financial institutions. Operational risk has the possibility to lead to other bank risk and to influence the perceptions of the banks' main stakeholder group i.e. depositors. The rationale behind profiling depositors' behaviour during operational risk events will contribute toward constructing a revolutionised risk management model. A better indication of how depositors react during operational risk events may lead to better prediction of withdrawal risk within banks. Primary data was collected from 417 depositors in Gauteng, South Africa, using a self-structured questionnaire. Statistical techniques such as correlation and `significance tests were used in the statistical analysis. A positive relationship was found between depositor likelihood to withdraw during operational risk events for two of the three variables; bank perceptive and behavioural finance biases. A negative relationship was found between depositor's likelihood to withdraw and their risk tolerance level.
Keywords: G14; G21; C3; 330; operational risk; behavioural finance; risk tolerance; stakeholder perception